(untitled) (Journal of Oriental Studies, 2016)
In present article the author defines the nature of Islam’s politicization, analyzes the reasons and consequences of this process in territory of the Central Asian countries. Dissolution of bipolar system of the world and discredit of dominating communistic ideology are considered as the main stimulating factors of Islam’s politicization that has led «Islamic Renaissance» in this region. A negative consequence of Islam’s politicization was distribution of the extremist organizations of radical sense that threatens safety of the region’s countries.